Twinning in structural material with a hexagonal close-packed crystal structure - Leo Prakash (The Journal of Strain Analysis for Engineering Design, 2010)
The paper aims to provide a brief and comprehensible overview of the current understanding of twin nucleation and growth in structural metallic materials with a hexagonal close-packed crystal structure. It describes possible experimental methods to improve this understanding, which is required to implement twin nucleation and growth in crystal plasticity models using mechanistically meaningful criteria. These aspects are further discussed by presenting results from deformation experiments carried out on a zirconium alloy (ZIRLO™) and Ti–6 wt% Al–4 wt% V (Ti–6Al–4V). It is shown that very significant texture changes after even small levels of plastic deformation can be observed in both materials, strongly suggesting the presence of extensive